The Relationship between Religiosity and Academic Stress of North Sumatra Islamic Center Students - Salmah Siregar; Ali Daud Hasibuan (Universitas Muhammadiyah Enrekang, 2024)
Abstrak Stress akadmeik menjadi permasalahan yang ekrap dialami para siswa dewasa ini, terutama siswa yang memiliki padat aktivitas. Penelitian ini bertujuan untuk emgetahu hubungan religiusitas dengan stres akademik. Pendekatan penelitian menggunakan kuantitatif jenis korelasional. Populasi penelitian ini seluruh siswa/peserta didik di Islamic Centre. Sampel diambil secara random berjumlah 287 orang. Instrumen penelitian adalah angket tentang religiusitas dan stres akademik. Teknik analisis data menggunakan deskripsi data dan uji hipotesis dengan uji korelasi product moment. Hasil penelitian menunjukkan adanya hubungan negatif antara religiusitas dengan stres akademik. Artinya, jika skor religiusitas meningkat maka skor stres akademik menurun, sebaliknya jika skor religiusitas menurun maka skor stres akademik meningkat. Melalui hasil penelitian tersebut, dipeoleh hubungan antar kedua variabel sebesar -0,341 pada signifikansi 0,003 < 0,05. Dapat disimpulkan bahwa religiusitas degan stress akademik memiliki hubungan yang negatif. Kata Kunci: hubungan, religiusitas, stress akademik Abstract Academic stress is a problem often experienced by students today, especially students who have busy activities. This research aims to determine the relationship between religiosity and academic stress. The research approach uses a quantitative correlational type. The population of this study were all students at the Islamic Center. Samples taken randomly amounted to 287 people. The research instrument was a questionnaire about religiosity and academic stress. The data analysis technique uses data description and hypothesis testing with the product moment correlation test. The research results show that there is a negative relationship between religiosity and academic stress. This means that if the religiosity score increases, the academic stress score decreases, conversely, if the religiosity score decreases, the academic stress score increases. Through the results of this research, the relationship between the two variables was obtained at -0.341 at a significance of 0.003 <0.05. It can be concluded that religiosity and academic stress have a negative relationship. Keywords: relationships, religiosity, academic stress